Numerical investigation of sediment scour downstream of adjustable and fixed submerged weir using FLOW-3D - Che Mohd Azmi, Siti Nurain; Ibrahim, Saerahany Legori; Ibrahim, Izihan; Masbah, Dani Irwan (IIUM Press, 2025)
Scouring downstream of hydraulic structures poses significant risks to structural stability and sediment transport processes in river systems. This study presents a numerical investigation of sediment scour behaviour downstream of two submerged weir types, adjustable submerged weirs (hydraulic tilting gates) and fixed submerged weirs (Crump weirs), using FLOW-3D software. Field measurements from Acoustic Doppler Current Profiler (ADCP) surveys were used to validate the hydrodynamic model, with a finer mesh size of 1.5 m achieving high accuracy (R² = 0.998, RMSE = 0.018 m). This mesh size was subsequently adopted for sediment transport simulations. The research focuses on evaluating velocity at the bed and scour depth under a range of flow discharge series, from 183.30 m³/s to 3666.00 m³/s, over a 2-year ARI for the Kelantan River, across 20 simulation runs, with low, moderate, and high discharges, classified using a percentile-based approach. The simulations adopt the Reynolds-Averaged Navier-Stokes (RANS) equations with the RNG turbulence model, coupled with the Meyer-Peter and Müller sediment transport formulation. Results reveal that the adjustable submerged weir generally produces higher bed-level velocities at low to moderate discharges, indicating a tendency toward more concentrated local scour. This is likely due to the flow being constricted and accelerated as it passes over and through the adjustable structure, thereby increasing shear stress on the bed. In contrast, the fixed Crump weir exhibits significantly higher peak velocities under extreme flow conditions, leading to broader but less focused erosion patterns, likely because its fixed geometry causes the flow to spread out more evenly downstream, reducing localised acceleration but increasing the overall area affected by erosion. Scour depth analysis reveals that the adjustable weir induces deeper scour holes, with a maximum depth of -5.917 m, whereas the fixed weir reaches a maximum depth of -4.128 m. These outcomes highlight the influence of structural geometry and operational flexibility on downstream hydraulic behaviour and sediment response